Analysis of use of the periodical collections of the Indonesian National Scientific Documentation Center (PDIN) and the Central Library of the Indonesian Institute of Sciences (PS LIPI) - Karwenda, Karyeti (1995)
This study analyzed the use of the periodical collections of the Indonesian National Scientific Documentation Center (PDIN) and the Central Library of Indonesian Institute of Sciences (PS-LIPI).The analysis was based on 537 questionnaires accomplished by users of the two libraries from 17 September to 16 October 1984 and observation and analysis of periodicals actually used and requests for photocopies of periodical articles serviced from 3 September to 10 November 1984. Most of the respondents were specialists in the areas of science and technology and social sciences and humanities. A few respondents were in the areas of biology and agriculture and health and medicine.